Through the Eyes of the User: Evaluating Neonatal Intensive Care Unit Design. (July 2018) - Denham, Megan E.; Bushehri, Yousef; Lim, Lisa
Objective: This article presents a pilot study that employed a user-centered methodology for evaluating and quantifying neonatal intensive care unit (NICU) designs based on the needs of the primary users. Background: The design of NICUs has begun to shift from open-bay to single-family rooms. Both designs present unique advantages and challenges that impact babies, families, and caregivers. Methods: One NICU design was analyzed using the functional scenario (FS) analysis method. For the FS, users' needs were determined through literature review, interviews with NICU providers and parents, and a review of published design guidelines. Quantitative metrics were developed for each FS, so that characteristics of the NICU design could be analyzed to determine how successful they were in meeting the users' needs. The results were graphically represented to visualize the success and considerations of the design. Results: A total of 23 FSs and 61 spatial metrics were developed. FSs for babies focused on infection prevention, minimizing exposure to environmental stimuli, and supporting enriching care activities. FSs for family members focused on direct access to the baby, and privacy and adequate space for daily activities. FSs for providers and caregivers focused on infection prevention, care activities, care zones, and visibility. Conclusion: Using an FS approach highlights design characteristics in the NICU that need to be addressed during the design process to more successfully meet the needs of the different users. Additionally, using this approach can inform design professionals' decision-making by presenting them with the design characteristics that impact the needs of the user groups.